PENGARUH CSR DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DAN UKURAN PERUSAHAAN - Elisabeth Hansel; Rini Tri Hastuti (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This study aims to analyze the influence of CSR and dividend policy on firm value with firm size as moderating variable. This research was conducted with purposive sampling. The analysis concluded that the CSR and dividend policy had a significant and positive effect on firm value that firm size as moderating variable from manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 as research samples.